KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE YANG DIPENGARUHI OLEH KUALITAS PRODUK DAN METODE PEMBAYARAN - Agus Sudigdo; Taufik Alwi; Irwan Kurniawan (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine the effect of product quality and payment methods on purchase decisions at marketplace Shopee Jakarta. The research method used is a quantitative research method. This research uses probability sampling method with cluster sampling technique and random stratified sampling with the number of respondents as many as 400 respondents. The data collection technique used a questionnaire which was processed using SPSS version 25. Data analysis used validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing consisting of t test, F test and R2 test. And the results show that the selected 2 independent variables (product quality and payment methods) simultaneously have a significant and significant effect on purchasing decisions. Then for the results of the partial study, the independent variables consisting of product quality and payment methods are positive and significant. And the R2 test value obtained in this study is 0.512, meaning that 51.2% of Purchase Decisions can be explained by product quality and payment methods and the remaining 48.8% explained by other variables that were not examined